"SERUM FERRITIN IN TYPE 2 DIABETES MELLITUS AND ITS RELATIONSHIP WITH HbA1c" - F. Sharifi Sh. Sazandeh (Acta Medica Iranica, 2004)
Diabetes mellitus (DM) type 2 is one of the most common endocrine disorders affecting more than 135 million people in the world. The etiology of the disease is not fully understood, but recently subclinical hemochromatosis has been considered as one of the probable causes of DM. This study was carried out to examine the relationship between serum ferritin as a marker of iron overload with DM and HbA1c. This study was conducted on 97 patients with type 2 DM who were referred to Zanjan Diabetes Clinic. Ninety-four normal age-matched individuals were included in the study as the control group. Ferritin, hemoglobin, HbA1c, and fasting blood sugar were measured in blood samples. Exclusion criteria included anemia, or any other disease or drug that could affect ferritin levels. Results were analyzed statistically by Chi-square test, t-test and Pearson regression coefficient test. One hundred ninety-one cases including 97 diabetics (37 males and 60 females) and 94 normal individuals were studied. There were no significant differences between the two groups regarding age, hemoglobin and body mass index. Mean serum ferritin was significantly higher in diabetics than in the control group (101±73 mg/ml vs. 43.5+42 mg/ml, p